Fatores de risco em pacientes com infecções hospitalares causadas por Klebsiella pneumoniae produtora de carbapenemase - Franchini, Fernanda Paula (2016)
Klebsiella pneumoniae carbapenemase producing Klebsiella pneumoniae (KPC-Kp) is an emerging pathogen with acquired resistance to several antimicrobial classes and produces infections associated with considerable mortality. This study aims to identify risk factors for acquisition of hospital infections caused by KPC-Kp and to identify the clinical outcomes of these patients. This is a case-control study performed at a tertiary teaching hospital with 365 beds. The cases with hospital infection caused by KPC-Kp were compared with controls admitted to the same hospital paired by gender, age group and admission entry in a proportion of 2:1. During the period from February 2013 to August 2014, 22 patients were included in the study as cases and 44 as controls. The following independent risk factors for acquisition of hospital infections caused by KPC-Kp were identified: presence of a central venous catheter (OR 21.89; 95% CI 3.7 129.0); admission in an intensive care unit (OR 8.05; 95% CI 1.5 43.2); use of beta-lactams associated with or without beta-lactamase inhibitors (OR 6.02; 95% CI 1.1 32.6); use of carbapenems (OR 11.01; 95% CI 2.1 58.0) and the use of polymyxin B (OR 15.74; 95% CI 1.3 194.2). The crude case mortality rate was 36.8% (P=0.004). Infections caused by KPC-Kp are severe with an elevated mortality. To avoid unnecessary usage of antimicrobials, mainly beta-lactams, carbapenems and polymyxin B appear to be an essential way to control these infections.